O gênero Richterago Kuntze (Gochnatieae: Asteraceae) na mesorregião do Campo das Vertentes - Biondi, Michel (2017)
With about 30,000 species divided into 1700 genera, the cosmopolitan Asteraceae dominates the globe with its diversity. However, this dominance becomes particularly more expressive in xeromorphic and campestral environments. The rupestrian fields, located in Brazil, are open phytophysiognomies, with environmental extremes. It makes these environments favorable for species with low nutritional demand and that are very resistant and resilient to environmental Inclement weather. The meso-region of Campo das Vertentes has a rugged relief with altitudes varying between 500 and 1500 meters. It is composed of the Bocaina Mountains Complex, Ouro Grosso and Carrancas mountains. On this places occurs the genus Richterago Kuntze (part of the complex Gochnatieae tribe), which is endemic of Brazil and intrinsically linked to the rupestrian grasslands. Based on this information, the objective of this work was to identify the Richterago species occurring in the region. In the mountain ranges of the complex, R. campestris Roque & J.N.Nakaj., R. discoidea (Less.) Kuntze and R. radiata (Vell.) Roque are found. In some localities these species occur in sympatry, which added to the geographic isolation of the hill tops, facilitates events of natural hybridization. The taxonomic result corroborates the distribution found in the literature, but the specimens with intermediate morphology in the sympatric populations feed the idea of natural hybridization.